THE FACTORS AFFECTING THE PERFORMANCE OFWOMEN ENTREPRENEURS IN LOKOJA: EVALUATING THE SOCIO-CULTURAL ISSUES AND LEVEL OF EDUCATION VARIABLES - OGARAKU, Nneoma Bridget; AYOZIE, Daniel Ogechukwu (EBSU Journal of Social Sciences and Humanities, 2024)
The study aimed at exploring factors affecting the performance of women entrepreneurs in Lokoja Kogi State. For the study, a survey research design was employed, using Taro Yamane formula to obtain a sample size of 190 from a population of 363 women entrepreneurs who are members of the Lokoja Business Women Association. The 190-sample size was selected using simple random sampling technique. Data was collected through well-structured questionnaires designed using five-point Likert scale, 184 questionnaires were returned out of the 190 distributed. Data was presented and analyzed using SPSS version 21 simple liner regression, Anova and path coefficient to determine the level of relationship between performance vis-à-vis access to finance, level of education, family commitment and socio-cultural factors affecting women entrepreneurs. To ensure reliability the researcher used Cronbach Alpha reliability test to obtain the level of reliability of the research variables. The study madeseveral findings which are that access to finance, level of education and socio-cultural factor have a positive and significant relationship with performance of women entrepreneurs while family commitment has a negative and significant relationship with the performance of women entrepreneurs. The study made the following recommendations among which are that government should make and implement policies and strategies that would give women equal access to education, productive resources like their male counterparts, government should provide interest free loans to help women entrepreneurs expand their businesses, women should invest in self development and build strong support network for their businesses.